THE ACCOUNTING VALUE RELEVANCE OF PSAK 71 - Susherwanto, Adi; Handayani, Rr. Sri (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
This study is to test whether PSAK 71 increases value relevance of earnngs, book value, and the combination of earnings and book value for banking companies listed on the Indonesia Stock Exchange for the period 2019 and 2020. The sample of this study was 92 banking companies. The sampling method is used in this study by universal sampling with several criteria. The data analysis method used is multiple regression analysis. The results of the regression tests indicate that PSAK 71 has value relevance on corporate earning. PSAK 71 also has value relevance on book value, However, PSAK 71 does not increase the relevance of earnings and book value, the result is a decrease in value relevance from any increase in earnings and book value. PSAK 71 also does not increase the value relevance of tcontrol variable Allowance for Impairment Losses (CKPN).